2019
DOI: 10.35741/issn.0258-2724.54.6.20
|View full text |Cite
|
Sign up to set email alerts
|

Family Business in Vietnam and in Poland: Review of Characteristics and Trends of Development

Abstract: Enterprise and entrepreneurship are well-known phenomena that have their history development of over 300 years. However, in relation to the family business they are still not well explored in the literature of management. Based on the overview of management literature, this article is an attempt to construct a theoretical framework for the purpose of comparative analysis of family business and entrepreneurship issues in Poland and in Vietnam. As a result, their similarities and differences are revealed in orde… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 44 publications
2
10
0
Order By: Relevance
“…The transition from a centrally planned to a free market economy led to a wave of new ventures (Cieslik and Kąciak, 2009), many of which were family businesses (Kowalewski et al, 2010;Baginska, 2019;Marjanski and Sułkowski, 2019). Tien et al (2019) describe the unique traits of Polish family firms, over erstwhile underdeveloped counterparts [like Vietnam], as their adaptability to a free market system and the benefit of assimilation into the common European market. Others cited peculiarities of family firms in Poland such as an advanced skills-set and competencies among the workforce, evident multiculturalism, planned intergenerational succession and gender equality in management and operations (Tien et al, 2019).…”
Section: The Research Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…The transition from a centrally planned to a free market economy led to a wave of new ventures (Cieslik and Kąciak, 2009), many of which were family businesses (Kowalewski et al, 2010;Baginska, 2019;Marjanski and Sułkowski, 2019). Tien et al (2019) describe the unique traits of Polish family firms, over erstwhile underdeveloped counterparts [like Vietnam], as their adaptability to a free market system and the benefit of assimilation into the common European market. Others cited peculiarities of family firms in Poland such as an advanced skills-set and competencies among the workforce, evident multiculturalism, planned intergenerational succession and gender equality in management and operations (Tien et al, 2019).…”
Section: The Research Contextmentioning
confidence: 99%
“…Tien et al (2019) describe the unique traits of Polish family firms, over erstwhile underdeveloped counterparts [like Vietnam], as their adaptability to a free market system and the benefit of assimilation into the common European market. Others cited peculiarities of family firms in Poland such as an advanced skills-set and competencies among the workforce, evident multiculturalism, planned intergenerational succession and gender equality in management and operations (Tien et al, 2019). Owing to being a relatively new market society, there is also a higher concentration of first-generation family businesses in Poland that have retained a controlling stake in the firm (Kubica and Szarucki, 2016).…”
Section: The Research Contextmentioning
confidence: 99%
“…This study argues that the male child is usually the preferred successor in Zimbabwean FOPBCs. These findings are in line with suggestions by Tien, et al, (2019) who noted that in most Asian countries, male supremacy also spills into family businesses. In their study, Chen et al, (2021) also reported that male family entrepreneurs in China dominated females.…”
Section: Gendersupporting
confidence: 92%
“…Therefore, they relied on experience which they gained in their previous employment as artisans. Some of the motivations for forming family-owned enterprises include the desire for financial autonomy, security, and pursuit of career choice (Tien et al, 2019).…”
Section: Founder Motivation To Start Business and Members Involvedmentioning
confidence: 99%
“…However, we can assume the majority of media family businesses as entrepreneurial businesses as well. In another research, researchers have identified trust as the critical element for sustaining and developing family businesses (Tien et al , 2019). Agbim (2018) also shares that trust and commitment are among the essential factors for the developmental visions of a family business.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%